Identifying chromosomal introgressions from a wild species Arachis diogoi into interspecific peanut hybrids. (12th May 2020) - Hanson, Erik; Zhou, Hai; Tallury, Shyamalrau P.; Yang, Xiping; Paudel, Dev; Tillman, Barry; Wang, Jianping
Abstract: An interspecific peanut hybrid population was generated from a cross between Arachis diogoi, a wild species with resistance to spotted wilt, and "Gregory", a susceptible cultivar. The objectives of the study are to identify successful introgression of A. diogoi's genome and to evaluate the spotted wilt resistance in the introgression population. Sixty‐three putative introgression lines were genotyped using 137 polymorphic simple sequence repeat markers, out of which 14 markers located on seven of the 20 peanut chromosomes showed introgression of A. diogoi genome into at least one of the introgression lines. In addition, genotyping by sequencing of a subset of the population revealed SNP loci displaying introgression of A. diogoi genome on every chromosome of the A sub‐genome of the introgression lines, with the most introgressed loci on chromosome A05. Several introgression lines showed consistent spotted wilt resistance, suggesting successful genomic introgression of A. diogoi contributing to the resistance.